Duodenal Perforation Secondary to Migrated Biliary Stent: A Rare and Serious Complication of Endoscopic Retrograde Cholangiopancreatography - Yagnik, Vipul D.; Joshipura, Vismit P. (Journal of Digestive Endoscopy, 2018)
Although migration of biliary stents is not uncommon, stent‑induced perforation of the intestinal wall is a rare and serious complication. We report a case of duodenal perforation secondary to migrated biliary stent kept for obstructive jaundice for common bile duct stone in a 64‑year‑old male. Intestinal perforation secondary to migrated stent should be considered in patients reported with abdominal pain and sepsis after an endoscopic retrograde cholangiopancreatography with biliary stent placement.
Keywords: Biliary stent; duodenal perforation; endoscopic retrograde cholangiopancreatography